Perancangan Alat Proteksi Tegangan Listrik Berlebih dan Menurun pada Jaringan Distribusi Tegangan Rendah - Pirza Hariyanto; Sepdian; Mahmud Idris; Maizal Isnen (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2020)
In a basic electricity network, the quality of electric power distribution is needed. There are also obstacles in the distribution of electric power that can affect, let alone damage, the electric power system. If this voltage constraint is connected to electrical or electronic equipment and exceeds the nominal voltage tolerance limit, it can interfere with the performance of the equipment or moreover it can damage it. From the testing of the Arduino uno microcontroller-based under / over voltage relay tool, it can be concluded that the under / over voltage relay device designed and made can work properly, in the sense that this tool can detect an under voltage of -5% and an over voltage of +5. % of nominal voltage and able to activate the fault indicator light and sound an alarm when the under / over voltage setting is exceeded